Occurrence of Selected Metals in Wastewater Effluent and Surface Water in Ireland - Jones, L.; Sullivan, T.; Kinsella, Brian; Furey, A.; Regan, F. (Taylor & Francis Inc., 2017)
© 2017 Taylor & Francis. Metals occur naturally in the environment and as constituents of the Earth’s crust. They have many uses, and metals such as iron, copper, and zinc are widely used in industries. Elevated levels of metals in the environment also occur as a result of human activities (municipal, residential, and traffic–related activities). A list of 15 metals chosen for this study included priority substances and those listed in the European Union Water Framework Directive 2000/60/EC. The concentrations of heavy metals in the environment are affected by several factors that must be taken into account when monitoring heavy metals released into the environment through wastewater treatment plants (WWPTs). This work examines the concentrations of metals found in WWPTs and the effects of treatment type on dissolved metal concentrations. Effluent samples were collected from the outflow of nine WWPTs in Dublin and Cork, Ireland from July 2009 to June 2011. All samples were found to contain priority metals that exceeded environmental quality standards in several cases. We present the frequency of occurrence and concentrations of metals in effluents of studied WWPTs and discuss relationships between the occurrence of heavy metals, the influence of factors such as industrial inputs, levels of treatment at WWPTs, and percentage urban area in an agglomeration. The results of this study are an indication that WWPTs may be contributing to the high levels of heavy metals found at discharge points back into river systems.